How Does Internet Usage Influence Young Travelers' Choices?. (June 2019) - Hong, Jinhyun; McArthur, David Philip
New technologies have significant effects on travel behavior, attitudes, habits and potentially future travel demand. Effects may be more prominent for Millennials. Little empirical research has investigated these relationships, mainly due to data limitations. This study focuses on the potential influence of using the Internet while traveling on Millennials' plans for car ownership. We examine two questions: Does using the Internet while traveling influence trip frequencies? and Does it affect Millennials' intention to purchase a car? Results suggest that Internet use while traveling is positively associated with travel demand and the intention to purchase a car in the near future.